Effect of postdose fasting duration on hetrombopag olamine pharmacokinetics and pharmacodynamics in healthy volunteers. Issue 8 (8th March 2020) - Yang, Guoping; Huang, Ranglang; Yang, Shuang; Zhang, Xingfei; Yang, Xiaoyan; Chen, Honghui; Huang, Zhijun; Guo, Chengxian; Pei, Qi; Tai, Yanfei; Shen, Yancong; Huang, Jie; et al.
Abstract : Aims: Hetrombopag olamine is a novel small‐molecule, nonpeptide thrombopoietin receptor agonist developed for immune thrombocytopenia treatment. This study aims to determine the safety and the effect of fasting duration after administration of hetrombopag on pharmacokinetics and pharmacodynamics in Chinese healthy subjects. Methods: A randomized, open‐label, single‐dose, 3‐period crossover, self‐control trial was conducted. 15 eligible subjects were enrolled and received hetrombopag 7.5 mg at day 1 of each period followed by a standard meal 4 hours postdose (treatment A/fasting condition), or a high‐calorie, high‐fat meal 1 hour postdose (treatment B), or a high‐calorie, high‐fat meal 2 hours postdose (treatment C). The plasma concentrations of hetrombopag were determined by validated liquid chromatography–tandem mass spectrometry, platelet counts were quantified by blood test. Analysis was performed using a mixed model, including treatment, period as fixed effects and participant as a random effect. Results: Compared with treatment A, peak concentration and area under concentration–time curve extrapolated to infinity decreased by 56 and 74.6%, and 44 and 61% in treatments B and C, respectively. The mean platelet number on day 6 increased by 15.8, 6.96 and 10.26%, respectively, in treatments A, B and C in comparison with baseline platelet level. No severe adverse events happened in any of the 3 treatments. Conclusion: Hetrombopag was well tolerated in healthy male subjects under fasted/fed conditions. The shorter fasting duration resulted in lower hetrombopag exposure, corresponding to a lower level of platelet elevation. Therefore, we recommended oral administration of hetrombopag on an empty stomach (fasting condition) or at least 2 hours before a meal to achieve maximum bioavailability.